2009
DOI: 10.1371/journal.pone.0006243
|View full text |Cite
|
Sign up to set email alerts
|

Unscented Kalman Filter for Brain-Machine Interfaces

Abstract: Brain machine interfaces (BMIs) are devices that convert neural signals into commands to directly control artificial actuators, such as limb prostheses. Previous real-time methods applied to decoding behavioral commands from the activity of populations of neurons have generally relied upon linear models of neural tuning and were limited in the way they used the abundant statistical information contained in the movement profiles of motor tasks. Here, we propose an n-th order unscented Kalman filter which implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
151
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(163 citation statements)
references
References 62 publications
7
151
0
1
Order By: Relevance
“…Unfortunately, since speed is a nonlinear transform of velocity, this implies that linear decoders such as the Kalman filter (Wu and Hatsopoulos 2008) may not actually be optimal when based on TC or LFP H inputs. However, nonlinear state-space algorithms abound and have proven fruitful in decoding applications (e.g., Koyama et al 2010;Li et al 2009;Brockwell et al 2004;Shpigelman et al 2008;Dethier et al 2013). Another approach to accounting for speed in improving BMI control would be to treat it as a "nuisance variable," and use latent variable approaches to mitigate its effect on decoding (Lawhern et al 2010;Paninski et al 2010).…”
Section: Different Neural Origins For Different Neural Signal Modalitmentioning
confidence: 99%
“…Unfortunately, since speed is a nonlinear transform of velocity, this implies that linear decoders such as the Kalman filter (Wu and Hatsopoulos 2008) may not actually be optimal when based on TC or LFP H inputs. However, nonlinear state-space algorithms abound and have proven fruitful in decoding applications (e.g., Koyama et al 2010;Li et al 2009;Brockwell et al 2004;Shpigelman et al 2008;Dethier et al 2013). Another approach to accounting for speed in improving BMI control would be to treat it as a "nuisance variable," and use latent variable approaches to mitigate its effect on decoding (Lawhern et al 2010;Paninski et al 2010).…”
Section: Different Neural Origins For Different Neural Signal Modalitmentioning
confidence: 99%
“…It has been previously shown that hand velocity can be predicted from motor cortical ensemble activity (Georgopoulos et al, 1988;Schwartz, 1994;Lebedev et al, 2005;Li et al, 2009). To determine whether this model was also applicable during IT periods, we trained an LGF decoder (Koyama et al, 2010a,2010b) using the velocity tuning model (decoder configuration D1, see Materials and Methods).…”
Section: Continuous Decoding Including During It Periodsmentioning
confidence: 99%
“…Antes de comenzar con la decodificación debe elegirse el tipo de modelo que se empleará. Entre las elecciones más usuales destacan los filtros lineales, especialmente el de Wiener [12], [13] y el de Kalman [14], [15].…”
Section: Decodificaciónunclassified